Perspectives of School Principals and Geography Teachers on Sustainable Development Goals - Kandangama, K G C (ASEAN Multidisciplinary Research Journal, 2022)
Education for Sustainable Development (ESD) is crucial for developing younger generation’s kowlegede, attitudes and skills towards social, economic and environmental development. Objectives of this study were to identify school principals’ perspectives of ESD, to identify Geography teachers’ perspectives of ESD, to make suggestions to introduce SD goals in the school curriculum through the subject Geography. Research method used was survey method. Selected 1AB & 1C 32 schools under stratified sampling method from the Kandy District in Sri Lanka. As research tools questionnaire and interview schedule were used for both teachers and school principals. Data analyzed qualitatively and quantitatively. According to results 74.36% of teachers, 60% of principals have strongly agreed SD concept is worth paying attention to and 54.3% of teachers, and 42.9% of Principals have strongly agreed ESD concepts should be taught during school hours. According to the principal’s perspectives, school time should be utilized to transfer knowledge, attitudes and skills towards ESD .As teacher’s perspective, school is the only place to provide knowledge skills and attitudes regarding ESD and to give practical knowledge about ESD beyond text books to develop good qualities as responsible citizens. As conclusion, SD should be included into subject Geography while introducing SD Goals. Suggestions were to make awareness programmes for teachers and principals about ESD and SD goals. Further, to pay much attention to school authorities to add ESD related knowledge, skills and attitudes into Geography curriculum as well as other subjects also mentioning SD Goals.